The Concept of Entrepreneurship Model from an Islamic Perspective: Konsep Model Kewirausahaan dalam Perspektif Islam - Rizky, Mochammad; Fikriyyah, Dzakiroh; Farid , Mifta; Adzani , Ridho; Maharani , Fridalifia; Eko , Aris; Efendi , Sofyan; Rahmawati, Imelda Dian (Journal of Islamic and Muhammadiyah Studies, 2024)
This research explores the concept of entrepreneurship within an Islamic framework, emphasizing the integration of religious elements and values to facilitate human self-development in business endeavors. Utilizing a document/text study research method, the investigation reveals that sincere adherence to Islamic teachings imbues entrepreneurial activities with a sense of worship, fostering qualities such as trustworthiness, kindness, and service orientation. Moreover, the study highlights the significance of activating Islamic spiritual intelligence to align business practices with religious principles, asserting that entrepreneurial success hinges upon individuals possessing an entrepreneurial spirit grounded in Islamic values. The findings underscore the importance of traits such as self-confidence, initiative, and risk-taking in Islamic entrepreneurship, ultimately contributing to a deeper understanding of entrepreneurial dynamics within the Islamic context and offering guidance for Muslim entrepreneurs in navigating their ventures. Highlights: Integration of Islamic values: Embedding trustworthiness and service orientation in entrepreneurship. Harnessing spiritual intelligence: Utilizing Islamic teachings to align business practices for success. Guidance for Muslim entrepreneurs: Offering insights for business rooted in faith-based principles. Keywords: Entrepreneurship, Islam, Perspective